TESTOSTERONE AND SOCIAL HIERARCHIES: FROM NEURAL MECHANISMS TO BEHAVIOURAL OUTCOMES - Khadijah Abdullah Md Harashid; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman; Usman Jaffer, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Testosterone is traditionally linked to aggression and dominance, yet growing evidence indicates that its influence on social behaviour is multifaceted. This review synthesizes key findings on testosterone’s role in shaping both aggressive and prosocial forms of dominance, drawing from animal and human research. Three cornerstone papers—Watanabe and Yamamoto (2015), Terburg and Van Honk (2013), and Johnson et al. (2012)—provide a foundation for understanding how testosterone interacts with multiple neural circuits, notably the amygdala, prefrontal cortex, and reward systems. These interactions can diminish inhibitory control while heightening reward sensitivity, thereby encouraging approach-oriented behaviours. However, whether elevated testosterone fosters aggression or prosocial leadership depends on contextual and individual factors, including personality traits and cultural norms. Baseline testosterone levels reliably predict discomfort in low-status positions and a drive toward higher social standing. Nevertheless, testosterone’s effects are shaped by complex interplays with cortisol, vasopressin, dopamine, and serotonin—emphasized by the dual-hormone hypothesis and recent neuroendocrine models. Methodological variations, such as hormone measurement techniques and experimental designs, contribute to conflicting findings in the literature. Recognizing testosterone as a dynamic modulator of social behaviour rather than a unidimensional “aggression hormone” broadens our understanding of human social hierarchies. Future research should employ longitudinal designs, cross-cultural studies, and advanced neuroimaging to unravel how testosterone’s nuanced effects can manifest in aggression, assertiveness, or cooperative leadership. This multi-level approach holds promise for improving theoretical models of social hierarchy and informing practical interventions in domains such as organizational leadership and mental health.